Estimation of Interleukin‐10 and Interleukin‐22 Levels in the Advances of Breast Cancer - Ali Jabbar Abd Zaid Al-Kilabi; Ghada Basil Ali Alomashi (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Breast cancer is the secant-kind of carcinoma in women with higher incidence in Iraq.There are many prognostic and predicitive factors used for management of the breast cancer. Serumlevels of the cytokines may be utilized as a marker of immunity status and prognosis in CA breast.Aims of the Study: Measuring the IL-10 and IL-22 in breast cancer patients and association IL-10and IL-22 with stage and grade for breast cancer. Materials and Methods: The case-control studywas conducted on 60 women with CA. Breast and 60 controls group, patients with CA. Breast werereferred to Middle Euphrates cancer center in Najaf during the period November 2019-October 2020.Measurement of Interleukin-10 and Interleukin-22 by using ELISA. Results: The showed a levels ofIL-10 and IL-22 in breast cancer group higher than levels of IL-10 and IL-22 in control, and showeda high levels of IL-22 in advances stage and grade III. The showed non-significant in IL-10 levelsbetween four stages and three grade. Conclusions: A significant elevation levels of IL-10 and IL-22 inbreast cancer groups comparison with control, elevation significant IL-22 levels in stages and gradesof breast cancer.